Green recovery: catalyst for an enhanced EU role in climate and energy policy? - Quitzow, Rainer; Bersalli, Germán; Lilliestam, Johan; Prontera, Andrea (Handbook on European Union Climate Change Policy and Politics, 2023)
This chapter reviews how the European Union has fared in enabling a green recovery in the aftermath of the Covid-19 crisis, drawing comparisons to developments after the financial crisis. The chapter focuses on the European Commission and its evolving role in promoting decarbonisation efforts in its Member States, paying particular attention to its role in financing investments in low-carbon assets. It considers both the direct effects of green stimulus policies on decarbonisation in the EU and how these actions have shaped the capacities of the Commission as an actor in the field of climate and energy policy. The analysis reveals a significant expansion of the Commission’s role compared to the period following the financial crisis. EU-level measures have provided incentives for Member States to direct large volumes of financing towards investments in climate-friendly assets. Nevertheless, the ultimate impact will largely be shaped by implementation at the national level.<br
Keywords: European Union; Green recovery; Covid-19 crisis; Climate finance; European Green Deal; Just transition